ERCP in Portugal: A Wide Survey on the Prevention of Post-ERCP Pancreatitis and Papillary Cannulation Techniques - Lopes, Luís (2019)
Background/Aims: Recently the European Society of Gastrointestinal Endoscopy delivered guidelines on the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) and on the papillary cannulation and sphincterotomy techniques at endoscopic retrograde cholangiopancreatography (ERCP). There are no data concerning current practices in Portugal. The aim of this study was to capture practice patterns of Portuguese pancreaticobiliary endoscopists with special interest in the prevention of PEP and cannulation techniques. Methods: A written survey was distributed to all pancreaticobiliary endoscopists attending the first Portuguese meeting dedicated to ERCP in November 2016. The main outcome measures were: technique used for standard biliary cannulation, use of nonsteroidal anti-inflammatory drugs (NSAIDs) in PEP, attempting prophylactic pancreatic stenting after using pancreatic guidewire (PGW)-assisted biliary cannulation in patients where biliary cannulation was difficult, and use of precut as the first rescue technique when biliary cannulation was difficult. Results: Completed surveys were collected from 28 of the 32 pancreatobiliary endoscopists attending the meeting (answer rate 87.5%). Biliary cannulation was performed using a guidewire access technique by the majority (77%), usually with a sphincterotome. When cannulation was unsuccessful, precut was the first choice for 70%. NSAIDs were administered routinely for PEP by only 54%; PGW-assisted biliary cannulation was the first choice after failed standard cannulation for a minority of them, and only 27% reported to routinely attempt insertion of a pancreatic stent. High-volume endoscopists (> 150/year) tended to use NSAIDs and to insert a stent in PGW-assisted cannulation less often than low-volume-endoscopists (50 vs. 83.3%, p < 0.01, and 40 vs. 100%, p < 0.01, respectively). Precut was started without prior formal training by more than half of the endoscopists. Conclusions: There is a pronounced discrepancy between evidence-based guidelines and current clinical practice. This discrepancy is more pronounced in PEP prophylaxis, especially among high-volume endoscopists. Some advanced techniques in ERCP are initiated unsupervised, without any previous formal training. Key Message: There is a significant gap between guidelines and routine clinical practice